Desenvolvimento de um Sistema IoT para o controle de iluminação residencial baseado nos princípios Indústria 4.0 - LOBATO, Elen Priscila de Souza (2023)
This paper presents the development of an Internet of Things (IoT) system for the control and activation of the residential lighting circuit, with dual communication, being Bluetooth Low Energy (BLE) and WiFi. The developed system was installed in the model of a home and building were used: an ultra-low energy ESP 32 DEV KIT V1 module, Solid State Relay (SSR) modules, BLE Scanner apps, MQTTDash and the Cloud to CloudMQTT. Thus enabling the control of lights both in person and remotely. Unifying all these technologies, the developed IoT system has interoperability, real-time operation and decentralization, which are principles of the Fourth Industrial Revolution, also called Industry 4.0 (I4.0). In addition, the system also directly applies the use of Automation, Cloud Computing and IoT, which are some of the pillars of I4.0. A laboratory experiment was also performed to measure the consumption of the system created and which type of communication (BLE or WiFi) consumes the least energy. So, in essence, the system is already energy efficient, because of its component technologies and its intended application - controlling the lighting circuit - also helps to promote Energy Efficiency (EE) as it can prevent lights stay on unnecessarily. On top of all this, the system is low cost.